High-loading lateral Li deposition realized by a Scalable Fluorocarbon Bonded Laminates. (January 2021) - Ren, Feihong; Li, Zhendong; Huai, Liyuan; Ren, Zhongmin; Wang, Muqin; Liu, Jian; Lin, Huan; Peng, Zhe; Wang, Deyu
Abstract: High-energy-density lithium (Li) metal batteries (LMBs) have been intensely revisited in recent years due to the urgent need of advanced energy storage technologies. However, a step towards the practical application of LMBs is still plagued by the lack of scalable method for Li metal protection. Rationally designed carbon nanostructures have been employed to stabilize Li metal anode, but only demonstrated as model structures without scalable productions. Herein, a type of fluorocarbon (–CFx ) bonded carbon nanoparticles is developed, which not only exhibit much better manoeuvrability to form uniform and crack-free laminates as large-area Li protective structure, but the presence of –CFx also leads to the formation of a high-content lithium fluoride (LiF) interphase via a lithiation route, endowing high-loading lateral Li deposition by the increase of interfacial energy between the substrate and the highly fluorinated interphase. Based on the efficacious Li protection by the –CFx bonded carbon laminates, a stable cycling of 300 cycles is achieved for Li||LiNi0.88 Co0.09 Al0.03 O2 (NCA) full cell with a high NCA loading of 5 mAh cm −2 . These results demonstrate that protecting high-loading Li metal anodes in the practical LMBs is feasible by the functional carbon synthesized from our easy-scalable method. Graphical abstract: Image 1